PENERAPAN PENDEKATAN SAINTIFIK DENGAN MEDIA AUDIO VISUAL DALAM PENINGKATAN PEMBELAJARAN MATEMATIKATENTANG BANGUN DATAR SISWA KELAS VSD NEGERI 2 BUMIREJO TAHUN AJARAN 2015/2016 - Al Imam, Muhamad As?ad (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Scientific Approach Using Audio Visual Media in Improving Mathematics Learning about Two-Dimensional Shape for the Fifth Grade Students of SD Negeri 2 Bumirejo in the Academic Year of 2015/2016. The objective of this research is to improve Mathematics learning about two-dimensional shape through the application of Scientific Approach using audio visual media for the fifth grade students of SD Negeri 2 Bumirejoin the academic year of 2015/2016. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles. Each cycle consisted of planning, action, observation, and reflection.Subjects of the research were 25 students of the fifth grade of SD Negeri 2 Bumirejo. Sources of data were derived from fifth grade students, teacher, researcher, observer, and documents. Validity of data in this research was analyzed using triangulation of sources and triangulation of technique.The conclusion of this research is the application of Scientific Approach using audio visual media can improve Mathematics learning about two-dimensional shape for the fifth grade students of SD Negeri 2 Bumirejoin the academic year of 2015/2016.Keywords: scientific approach, audio visual media, two-dimensional shape Abstrak: Penerapan Pendekatan Saintifik dengan Media Audio Visual tentang Bangun DatarDalam Peningkatan Pembelajaran Matematika Siswa Kelas VSD Negeri 2 Bumirejo Tahun Ajaran 2015/2016.Tujuan penelitian ini untuk meningkatkan pembelajaran Matematika tentang bangun datar dalam penerapan pendekatan Saintifik dengan media audio visual pada siswa kelas V SDN 2 Bumirejo Tahun Ajaran 2015/2016. Penelitian Tindakan Kelas (PTK) kolaboratif ini dilaksanakan dalam 3 siklus, yang terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalahsiswa kelas V SDN 2 Bumirejo tahun ajaran 2015/2016 yang berjumlah 25 siswa. Sumber data penelitian ini adalah siswa kelas V, gurukelas V,peneliti, observer, dan dokumen. Validasi data pada penelitian ini menggunakan tekniktriangulasi.Simpulan penelitian ini adalah penerapan pendekatan Saintifik dengan media audio visual dapat meningkatkan pembelajaran Matematika tentang bangun datar siswa kelas V SDN 2 Bumirejo Tahun Ajaran 2015/2016.Kata kunci: pendekatan Saintifik,media Audio Visual, Bangun Datar